THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON THE PERFORMANCE OF TEGALWARU VILLAGE OFFICE EMPLOYEES, CILAMAYA WETAN DISTRICT - Fazri Nurhasyim; Wanta Wanta; Nandang Nandang (Jurnal Ekonomi, 2023)
This study aims to explain the effect of organizational culture and work motivation on employee performance at the Tegalwaru Village Office, Cilamaya Wetan District, both partially and simultaneously, using descriptive and quantitative approaches. The number of samples is 79 respondents using a saturated sampling technique (census). Furthermore, the data was analyzed by path analysis (path analysis). The results of the research data analysis obtained the following conclusions: (1) The organizational culture at the Tegalwaru Village Office was good. (2) Work motivation at the Tegalwaru Village Office is good. (3) The performance of employees at the Tegalwaru Village Office is good. (4) There is a very strong correlation between organizational culture and work motivation of 0.829. (5) The influence of organizational culture on employee performance is obtained by sig. (0.000) < α (0.05) and tcount (3.865) > ttable (1.665) then Hodi Rejected, meaning that organizational culture partially affects employee performance. (6) The effect of work motivation on employee performance is sig. (0.000) < α (0.05) and tcount (3.988) > ttable (1.665) then Hodi Rejected, meaning that work motivation partially affects employee performance. (7) The influence of organizational culture and work motivation on employee performance obtained sig. (0.000) <α (0.05) and Fcount (90.017) > Ftable (3.12) then Hodi Rejected, meaning that organizational culture and work motivation simultaneously influence employee performance.